Penyuluhan Pemanfaatan Kacang Hijau dan Daun Bayam Sebagai Produk Minuman Serbuk Herbal “BHESTI” dalam Upaya Pencegahan Stunting di Desa Way Galih, Lampung Selatan - Intan kusuma wardani; Putri, Refsya Azanti; Andrea, Nabila; Putri, Suci Ananda; Ramdhani, Adean Naufal; Tsamarah, Dinda Taqiyyah; Adyani, Made Ninta; Khasanah, Zahrotun; Dzafitri, Rizka; Hindyana, Daffa Aqilla; Rahmawati, Winda; Safitri , Regif Desty; Sifana, Afiqa Najla; Faridah, Adinda Fitri Nur (Jurnal Dimas, 2024)
Stunting is a condition where toddlers fail to thrive due to prolonged chronic malnutrition and repeated exposure to infections, especially in the first 1000 days of life (HPK), resulting in short growth in children who do not meet standards. Based on Riskesdas data, the stunting rate in 2023 will reach 21.6% and every year the stunting rate in Indonesia continues to decline. One of the vegetable or legume commodities that is useful in fulfilling nutrition during the growing period is spinach leaves and soybeans. This is because green beans contain complete protein, namely calcium, potassium, phosphorus, iron, vitamins A, B, C. , E, and K. Apart from that, the nutritional content of spinach includes vitamins and minerals, including vitamins A, B, C, protein, fat, carbohydrates, potassium, calcium, phosphorus and iron. One local food product that is well received by the public is a drink in the form of herbal powder with the main ingredients being green beans and spinach leaves. This community service (PkM) activity was carried out to introduce the results of innovations in making products that can be produced independently by the people of Way Galih Village, Tanjung Bintang District, South Lampung Regency. This activity consists of three stages including preparation, implementation and evaluation stages. The results of this activity are an increase in the understanding of the Way Galih Village community regarding education about stunting as well as nutritional information needed by children during the growth period which can be obtained through foods that are easy to find in everyday life such as green beans and spinach.